Mediastinal Cystic Teratoma with Right Sided Extra Renal Wilms’ Tumor - A Rare Case Report (Bangladesh Journal of Child Health, 2018)
A teratoma of the mediastinum is an uncommon germ cell tumor. Five percent of germ cell tumors are extragonadally located and men are affected more than women .Most mediastinal teratoma produce no symptoms, but we are presenting a case which was present with respiratory distress in early childhood. Classical wilm’s tumor usually found within the kidney but rarely it can occur in extra renal situations. Combination of these two is not reported until today we have searched extensively. We are presenting a 26 month old boy with mediastinal cystic teratoma with right sided extra renal wilms’ tumor which may be the first reported case. Combined effort of various concern departments ensures the diagnosis and management of such a rare case.Bangladesh J Child Health 2018; VOL 42 (3) :155-158